2016
DOI: 10.3390/ma9090715
|View full text |Cite
|
Sign up to set email alerts
|

Formation and Entrapment of Tris(8-hydroxyquinoline)aluminum from 8-Hydroxyquinoline in Anodic Porous Alumina

Abstract: The formation and entrapment of tris(8-hydroxyquinoline)aluminum (Alq3) molecules on the surface of anodic porous alumina (APA) immersed in an ethanol solution of 8-hydroxyquinoline (HQ) were investigated by absorption, fluorescence, and Raman spectroscopies. The effects of the selected APA preparation conditions (galvanostatic or potentiostatic anodization method, anodizing current and voltage values, one- or two-step anodizing process, and sulfuric acid electrolyte concentration) on the adsorption and desorp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 28 publications
2
5
0
Order By: Relevance
“…The PL peak of the as-prepared APA sample (a) exhibits a peak at around 450 nm due to APA defects [29]. At 1 mM (b), the PL spectrum shows two peaks at 473 and 505 nm, which are the same results found in our previous study of APA treated in HQ in EtOH at 60 ∘ C [27]. The former and latter peaks are assigned to the isolated Alq 3 species in nanovoids, while the aggregated Alq 3 species are assigned to the nanopores in the APA.…”
Section: Effect Of Anodization Process On Crystal Morphology Andsupporting
confidence: 77%
See 1 more Smart Citation
“…The PL peak of the as-prepared APA sample (a) exhibits a peak at around 450 nm due to APA defects [29]. At 1 mM (b), the PL spectrum shows two peaks at 473 and 505 nm, which are the same results found in our previous study of APA treated in HQ in EtOH at 60 ∘ C [27]. The former and latter peaks are assigned to the isolated Alq 3 species in nanovoids, while the aggregated Alq 3 species are assigned to the nanopores in the APA.…”
Section: Effect Of Anodization Process On Crystal Morphology Andsupporting
confidence: 77%
“…As a result, there have been many studies of APA composites with highly fluorescent Alq 3 [22][23][24][25][26]. In a previous study, we reported that Alq 3 was formed on APA immersed in an ethanol solution of 8-hydroxyquinoline (HQ) at 60 ∘ C [27]. The PL spectra showed two peaks at wavelengths of 480 and 505 nm, which were attributed to isolated Alq 3 inside the nanovoids and aggregated Alq 3 in the nanopores of the APA, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…The luminescence quantum efficiency for the AlQ 3 in NOAQ material is about 2%, which is typical for AlQ 3 in an amorphous state [40][41][42]. One can see that for the NOAQ material, a blue-shift of the photoluminescence spectra is not observed (in comparison to the pure AlQ 3 complex) as it is for other similar systems [24,[43][44][45][46][47]. This is probably due to the high content of the complex in the pores of the NOAQ matrix, which makes its behavior close to the bulk AlQ 3 .…”
Section: Photoluminescent Propertiesmentioning
confidence: 76%
“…S1) is presently considered as one of the most reliable emitting materials because of its excellent stability and luminescent properties [22,23]. Immobilization of the AlQ 3 complex in porous matrices can serve as an alternative method for obtaining luminescent 3D materials for optical applications [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The applications of anodized aluminum include production of capacitors and abrasion resistant surfaces, coloring, and forming functional nanomaterials. In particular, anodic porous alumina (APA) films have recently gained attention in nanotechnology, because of their ordered pores and the excellent transparency of the APA film surface . As a result, APA is considered a promising platform for preparing optical applications. …”
Section: Introductionmentioning
confidence: 99%